2017
DOI: 10.15666/aeer/1504_19711982
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Evapotranspiration Based on Surface Energy Balance Algorithm for Land (Sebal) Using Landsat 8 and Modis Images

Abstract: Nouri et al.: Estimation of evapotranspiration based on Surface Energy Balance Algorithm for Land (SEBAL) Abstract. The aim of this study was to determine the accuracy estimation of actual evapotranspiration by using Surface Energy Balance Algorithm for Land (SEBAL) in comparison with FAO-Penman-Monteith method in Landsat and MODIS images in Malayer County of Iran. In this study, Landsat 8 and MODIS images of 2013 were used. Result showed that there are not many differences between SEBAL and FAOPenman-Montei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…For water resources planning on a large scale, point source measurement of ET will be impracticable due to constrains of time, human and financial resources. To overcome this challenge, the application of Geographic Information Systems (GIS) and Remote Sensing (RS) techniques in deriving the spatial distribution of continuous data for ET using surface energy balance techniques has been explored ( Allen et al., 2007 ; Bastiaanssen et al., 2005 ; Liou and Kar, 2014 ; Li and Zhao, 2010a , b ; Mkhwanazi et al., 2015 ; and Nouri et al., 2017 ). These GIS and RS techniques employ multi-spectral bands from satellite images to provide spatial information on ET over many regions ( Ayad et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For water resources planning on a large scale, point source measurement of ET will be impracticable due to constrains of time, human and financial resources. To overcome this challenge, the application of Geographic Information Systems (GIS) and Remote Sensing (RS) techniques in deriving the spatial distribution of continuous data for ET using surface energy balance techniques has been explored ( Allen et al., 2007 ; Bastiaanssen et al., 2005 ; Liou and Kar, 2014 ; Li and Zhao, 2010a , b ; Mkhwanazi et al., 2015 ; and Nouri et al., 2017 ). These GIS and RS techniques employ multi-spectral bands from satellite images to provide spatial information on ET over many regions ( Ayad et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Guzinski and Nieto's research shows that remote sensing technology can be used to estimate high-resolution evapotranspiration at the field scale with 85% accuracy compared with local meteorological observation and 81% accuracy compared with climate data analysis (Guzinski and Nieto 2019). Other studies show that remote sensing technology can estimate evapotranspiration at acceptable results (Nouri et al 2017;Li et al 2017) and do the goodness of fit compared with meteorological data analysis (Bonemberger et al 2018). Ceron et al 2015 reported that the evapotranspiration estimation based on remote sensing is better during the critical dry season when cloud cover is low (Ceron et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A estimativa desses componentes via sensoriamento remoto surge como uma alternativa eficaz e econômica diante da ausência de dados observados (Machado el at., 2014). O algoritmo SEBAL (Surface Energy Balance Algorith for Land), desenvolvido por Bastiaanssen et al (2005), a partir de imagens de satélite e poucos dados de superfície, vem sendo utilizado para esse fim (Nouri et al, 2017;Ogunjobi et al, 2018;Yang et al, 2018).…”
Section: Introductionunclassified